Análisis de la Eficiencia del Control Fiscal en los Entes Territoriales (2022)
The decentralization of the Colombian State in the Political Charter of 1991 starts from the definition of the territorial entities and the determination of the functions and mechanisms of the control organisms in the territories. With Law 42 of 1993, the organization of fiscal control is established in charge of the Comptroller General of the Republic and the territorial comptrollers functionally delimiting control activity, much of this in the principles of efficiency, economy, effectiveness, equity and cost valuation. environmental. This article aims to know the efficiency of the territorial control entities through a literary review of some authors who have carried out studies on the matter, making a discussion of the results found and finally the construction of a consideration as a conclusion, that allows to have a vision of what has been the decentralization of fiscal control in Colombia since the Political Constitution of 199